Diagnostic Value of Conventional and Digital Radiography for Detection of Cavitated and Non-Cavitated Proximal Caries - Mahdieh Dehghani; Rasool Barzegari; Hosein Tabatabai; Sahar Ghanea (Tehran University of Medical Sciences, 2017)
Objectives: This study aimed to assess the diagnostic value of conventional and digital radiography for detection of cavitated and non-cavitated proximal caries. Materials and Methods: Fifty extracted human premolars and molars were mounted in a silicone block. Charge-coupled device (CCD) and photostimulable phosphor plate (PSP) receptors and intra-oral films were exposed with 60 and 70 kVp with parallel technique. Two observers interpreted the radiographs twice with a two-week interval using a 5-point scale. Teeth were then serially sectioned in mesiodistal direction and evaluated under a stereomicroscope (gold standard). Sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated. Results: Sensitivity of all three receptors for detection of enamel lesions was low (5.5-44.4%) but it was higher for dentin lesions (42.8-62.8%); PSP with 70 kVp and 0.03s exposure time had the highest sensitivity for enamel lesions, but the difference among receptors was not statistically significant (P>0.05). Sensitivity of all three receptors for detection of non-cavitated lesions was lower than that for cavitated lesions; PSP with 60 kVp and 0.07s exposure time had higher sensitivity and lower patient radiation dose for detection of cavitated and non-cavitated lesions, but the difference was not significant (P>0.05). Conclusions: Digital radiography using PSP receptor with 70 kVp is recommended to detect initial enamel caries. For detection of non-cavitated and cavitated dentin caries, PSP with 60 kVp is more appropriate. Change in kVp did not affect the diagnostic accuracy for detection of caries, and type of receptor was a more important factor.